Inversion-based interpretation of 3D borehole directional resistivity measurements acquired in high-angle and horizontal wells - Puzyrev, Vladimir; Torres-Verdín, C. (2016)
We developed an efficient parallel 3D inversion method to estimate electrical resistivity from deep directional borehole electromagnetic (EM) induction measurements. The method places no restrictions on the symmetry of the assumed subsurface model and spatial distribution of electrical conductivity, and supports arbitrary well trajectories. Parallel direct solvers are employed for fast forward modeling of triaxial induction problems with multiple transmitter-receiver positions. Optimal transmitter-receiver configurations for several induction frequencies are determined for different application conditions. Numerical inversion results of challenging synthetic data confirm the feasibility of full 3D inversionbased interpretations, thus opening the possibility of integrating directional induction measurements with seismic amplitude data for improved petrophysical and fluid interpretations.